Hubungan Tingkat Literasi Ibu pada Balita terhadap Keaktifan Kunjungan Posyandu : The Relationship between Maternal Literacy Levels in Toddlers and the Activeness of Integrated Healthcare Center Visits - Fitriani, Ervina; Yuliza, Emi; Rokhmiati, Eka (Journal of Nursing Education and Practice, 2023)
Introduction: Posyandu is one of the health service programs provided by the local village to make it easier for the community to check health, especially for pregnant women and toddlers, therefore the activeness of mothers and tollers is very important in this activity so that toddler nutrition is monitored and the health of pregnant women is monitored. Objectives: To determine the relationship between maternal literacy level in toddlers to the activeness of Integrated Healthcare Center visits. Method: Using a quantitative research type with an analytic survey design through a cross-sectional approach method, determining the sample using a total sampling technique, the instrument used was a questionnaire and univariate and bivariate analysis tools. Result: Based on the results of the study, it was obtained that the chi-square test obtained a p-value of 0.316 or equal to > 0.050. Conclusion: There is no relationship between the level of maternal literacy in toddlers to the activeness of visiting Posyandu Nusa Indah RW 03 Cigombong Village, Bogor Regency, this happens because in searching for health information, mothers use internet media rather than getting information directly through Integrated Healthcare Center.